High Resolution Manofluorographic Study in Patients With Multiple System Atrophy: Possible Early Detection of Upper Esophageal Sphincter and Proximal Esophageal Abnormality - Ueha, Rumi; Goto, Takao; Sato, Taku; Nativ-Zeltzer, Nogah; Shen, Shih Chieh; Nito, Takaharu; Belafsky, Peter C.; Yamasoba, Tatsuya (Frontiers in Medicine, 2018)
Introduction: Multiple system atrophy (MSA) has detrimental effects on swallowing function. The swallowing function of patients with MSA has not been systematically characterized and the underlying pathophysiological mechanisms of dysphagia remain poorly understood. Objectives: To investigate the characteristics of swallow function in MSA using high-resolution manofluorography (HRMF). Methods: We conducted a retrospective review of twenty-five MSA patients who underwent HRMF from 2016 to 2017. HRMF was utilized on patients with only oral diet (Functional Oral Intake Scale >3). Pharyngoesophageal and proximal esophageal pressure profiles were evaluated and compared to established normative data. The frequency and characteristics of upper esophageal sphincter (UES) and proximal esophageal abnormalities during rest and swallow were calculated. Results: The ages of patient cohort in our study ranged from 48-81 years (median 65 years) with male predominance (68%). We observed a distinct abnormal deglutitive proximal esophageal contraction (ADPEC) in 14 (56% of patients), which appears to reflect a discoordinated response of the striated muscle esophagus. Deficient UES relaxation duration, impaired UES relaxation, hypertensive resting UES pressure and hypotensive resting UES pressure were detected in 8 patients (32%), 3 patients (12%), 1 patient (4%), and 11 patients (44%) respectively. Conclusions: In patients with MSA, abnormal UES resting pressure is common. A discoordinated proximal esophageal pressure response was identified and may be a pathognomonic manometry finding for MSA. These findings may serve as indications of early stage swallowing dysfunction in patients with MSA.